The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1111/j.1749-6632.1998.tb08942.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Impact of the Announcement of a Fetal Abnormality on Pregnant Women and on Professionals

Abstract: The psychological impact of the announcement of a fetal abnormality after ultrasound examinations is examined in relation to the building up of the mother-child attachment. It represents the "psychological cost" of such techniques. Understanding the subjective experience of the patients could increase the effectiveness of clinical practice. We have assumed that the relationship between parents and professionals is a critical element that contributes to the establishment of an emotional link between the mother … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
13

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 8 publications
(7 reference statements)
0
38
0
13
Order By: Relevance
“…These researchers recommend further research into the area of bad news transmission using other research designs. Detraux et al 21 tabulated retrospective quantitative data from prenatal US diagnosis of fetal abnormality using a developmental psychology perspective. Rempel et al 22 explored the pregnancy decision-making processes of parents following an antenatal diagnosis of fetal congenital heart disease using a qualitative design, describing parents' postdiagnosis relationship and interaction patterns with health care professionals.…”
Section: Introductionmentioning
confidence: 99%
“…These researchers recommend further research into the area of bad news transmission using other research designs. Detraux et al 21 tabulated retrospective quantitative data from prenatal US diagnosis of fetal abnormality using a developmental psychology perspective. Rempel et al 22 explored the pregnancy decision-making processes of parents following an antenatal diagnosis of fetal congenital heart disease using a qualitative design, describing parents' postdiagnosis relationship and interaction patterns with health care professionals.…”
Section: Introductionmentioning
confidence: 99%
“…Thus the patients were though anxious it did not affect their satisfaction. This could be related to the fact that most patient from the study indicated that they would not hesitate if asked to undergo the procedure again in contradiction with the study by Detraux et al [10]. The patients' satisfaction could be, the healthcare personnel, related to them in a friendly manner and also they found the imaging room to be comfortable.…”
Section: Effects Of Anxiety On Patient's Satisfactionmentioning
confidence: 69%
“…5) in support of Detraux et al, [10] and Christaine et al, [11] who stated that major reasons why women are anxious during and after an ultrasound examination is because of the fear of the outcome of the examination. Distressor anxiety is not determined by the invasiveness or pain of the procedure as argued by Kowaleek et al [12] which supports the findings of this study.…”
Section: Post Procedural Anxietymentioning
confidence: 79%
See 1 more Smart Citation
“…Many studies have shown that the detection of an anomaly creates emotional disturbance for the mother and her partner. Various feelings such as anxiety, prostration, depression, and loneliness are generally found in such mothers 20 . In a group of 11 mothers who had a child with cardiopathy diagnosed before birth, Detraux et al 20 found that ultrasound examination appeared at first as a method to visualize the future child, and confront the anxiety-producing reality of fetal cardiopathy.…”
Section: Situation B: Routine Pregnancy Fetal Anomalies Foundmentioning
confidence: 99%